Qualitative and Quantitative study of Epipelic algae in Tigris River within Baghdad City, Iraq - Baghdad Science Journal (مجلة بغداد للعلوم, 2014)
The present study conducted to study epipelic algae in the Tigris River within Baghdad city for one year from September 2011 to August 2012 due to the importance role of benthic algae in lotic ecosystems. Five sites have been chosen along the river. A total of 154 species of epipelic algae was recorded belongs to 45 genera, where Bacillariophyceae (Diatoms) was the dominant groups followed by Cyanophyceae and Chlorophyceae. The numbers of common types in three sites were 47 species. Bacillariophyceae accounted 88.31% of the total number of epipelic algae, followed by Cyanophyceae 7.14 % and Chlorophyceae 4.55%. A 85 species (29 genera) recorded in site 1, 103 species (34 genera) in site2, 112 species (35 genera) in site3, 96 species (32 genera) in site4, and 85 species (29 genera) in site5. Spatial and temporal distributions of epipelic algae were noticed in this study. The higher total number of epipelic algae (91504.01cell cm-2) was recorded at site 5 in spring 2012, while the lower was (37017.98cell cm-2) in summer 2012 at site1. Some genera have recorded higher number species during the study period; these genera were Nitzschia, Navicula, Cymbella, Gomphonema, Synedra, Achnanthes, Oscillatoria, and Lyngbya. The study revealed that Bacillariophyceae were more prominent within all study sites and followed by Cyanophyceae, while a few numbers of Chlorophyceae was appeared.